ANALISIS KOMPARATIF PERKEMBANGAN ISLAMIC FINANCE DI MALAYSIA, ARAB SAUDI, DAN INDONESIA PERSPEKTIF SGIE 2024/2025 - Trisena, Puja; Irmawati, Irmawati; Utami, Amanda Tri (Taksasila Edukasi Insani, 2025)
This study aims to analyze and compare the development of Islamic finance in Malaysia, Saudi Arabia, and Indonesia based on the State of the Global Islamic Economy (SGIE) Report 2024/2025. A qualitative descriptive comparative approach is employed using secondary data obtained from the SGIE report, policy documents, and relevant publications. Data analysis is conducted through content analysis focusing on regulatory frameworks, institutional capacity, and market development of Islamic finance in each country. The findings indicate that Malaysia represents a regulatory-driven Islamic finance model supported by consistent regulations and an integrated Islamic financial ecosystem, while Saudi Arabia adopts a state-driven approach with strong government support within its economic transformation agenda. Indonesia reflects an emerging Islamic finance ecosystem with significant market potential but faces challenges related to policy coordination, market deepening, and Islamic financial literacy. The study highlights the importance of regulatory consistency, institutional strength, and long-term policy alignment in strengthening Islamic finance development.Keywords: Islamic finance, SGIE, GIEI, Islamic financial system, comparative analysis